Mobilizing communities and families for child mental health promotion in Canada: Views of African immigrants. (August 2022) - Alaazi, Dominic A.; Salami, Bukola; Gabriel Ojakovo, Oghenevwarho; Nsaliwa, Christina; Okeke-Ihejirika, Philomina; Salma, Jordana; Islam, Bonnieca
Highlights: The African immigrant population is increasing rapidly in Alberta and across Canada. African immigrants face barriers accessing mainstream mental health (MH) supports. Family-, community-, and structural-level stressors present challenges to child MH. Family-, community-, and structural-level strategies can help promote child MH. These strategies include measures to build and enhance resilience during childhood. Abstract: Available evidence in Canada suggests mental health disparities between immigrant and non-immigrant children. Children born to immigrants face a greater risk of poor mental health outcomes. However, these comparisons often mask important ethno-racial differences in mental health risks and outcomes among immigrant populations. Recent evidence suggests African immigrant children have some of the poorest social and mental health outcomes in Canada. Despite this awareness, research has yet to identify community-based strategies for addressing the stressors underpinning such outcomes. This study used data obtained from focus groups with African immigrant parents in Alberta, Canada, to identify child mental health stressors and child mental health promotion strategies in the African immigrant community. These strategies, thematically partitioned into family-, community-, and structural-level interventions, include building supportive parent–child relationships, strengthening resilience in childhood, economic empowerment of families, destigmatizing mental illness, influencing institutional policies and practices, supporting labour integration, and enhancing access to mental health supports. Ways in which policymakers and service providers can support child mental health promotion efforts in the African immigrant community are also discussed.